The ins and outs of the South Platte Basin - Brown, Jennifer, editor; Colorado Water Institute, Colorado State University, publisher (Colorado State University. Libraries, 2013)
Proceedings of the 24th annual South Platte Forum held on October 23-24, 2013 in Longmont, Colorado. Includes program and abstracts of presentations.
Proceedings of the 24th annual South Platte Forum
October 2013.
Keywords: Watershed management -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water -- Law and legislation -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water use -- South Platte River Valley (Colo. and Neb.) -- Congresses